Clinical Significance and Functional Insights of Tesmin in Hepatocellular Carcinoma - Lijun Cao; Lin Zhang; Siyu Liu; Xue Wang (Genetics Research)
Background. Tesmin, a 60 kDa protein encoded by the metallothionein-like 5 (MTL5) gene, plays a vital role in spermatogenesis and oogenesis. Recent research has unveiled its potential involvement in malignancies, although its impact on HCC remains poorly understood. Methods. In this study, we sought to elucidate the clinical significance of tesmin in HCC patients. We investigated the relationship between tesmin expression and the prognosis of individuals with hepatocellular carcinoma (HCC), as well as its potential role in tumor proliferation and invasion. Immunohistochemistry (IHC) was employed to assess the expression of tesmin in HCC tissues. Chi-square tests were conducted to analyze the correlation between tesmin expression and various clinicopathological features among HCC patients. For survival analysis, we employed the Kaplan–Meier method and conducted Cox regression analyses. To investigate the functional role of tesmin, we utilized shRNA constructs for transfection-mediated knockdown. Proliferation was assessed using the CCK-8 assay, and invasive capability was determined through Matrigel Transwell assays. Results. IHC results indicated that tesmin expression was prominently observed in cancerous tissue. Notably, we observed a significant association between tesmin expression and tumor stage and invasion in HCC patients from both our medical center and TCGA dataset. Survival analysis further revealed that tesmin expression emerged as an independent prognostic factor for overall survival among individuals with HCC. Furthermore, cellular experiments demonstrated that knockdown of tesmin led to decreased proliferation and invasion of HCC cells. Conclusions. Our findings suggest that tesmin may serve as a novel prognostic marker for HCC, highlighting its potential as a target for further research into HCC treatment. Additionally, the functional experiments support the notion that tesmin may participate in promoting the proliferation and invasion of HCC cells, warranting further investigations into its mechanistic involvement in HCC progression.